By His Excellency Thomas Pownall, Esq ; ... A proclamation : Whereas His Majesty by His Royal commission has been pleased to appoint me to be captain-general and governour in chief ... Given at the Council-chamber in Boston, the third day of August, 1757 . (Printed by John Draper, printer to his excellency the governour and the honourable his majesty's Council, 1757)
August 3, 1757 Proclamation by Governor Thomas Pownall that he is the new Captain-General and Governor in Chief of the Province of Massachusetts Bay and continuing all officers in their respective trusts.